2017
DOI: 10.1002/sctm.16-0438
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Efficacy of Intra-Arterial Administration of Mesenchymal Stem Cells in an Animal Model of Double Toxin-Induced Multiple System Atrophy

Abstract: Multiple system atrophy (MSA) is a sporadic neurodegenerative disease of the central and autonomic nervous system. Because no drug treatment consistently benefits MSA patients, neuroprotective strategy using mesenchymal stem cells (MSCs) has a lot of concern for the management of MSA. In this study, we investigated the safety and efficacy of intra‐arterial administration of MSCs via internal carotid artery (ICA) in an animal model of MSA. The study was composed of feasibility test using a ×10 and ×50 of a stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Nevertheless, while IV injection of stem cells may not be the optimal method for direct cell replacement, it has instead the potential to be highly effective for cells which primarily exert their therapeutic effect through long distance paracrine modulation, such as MSCs. Alternatively, intraarterial injection of stem cells has been proposed to prevent the collection of cells in systemic organs and increase the incidence of cells reaching their CNS targets (Walczak et al, 2008;Argibay et al, 2017;Na Kim et al, 2017). However, caution should be taken when using this administration route as it runs the risk of causing microembolisms if the volume and concentration of injected cells are not carefully controlled (Argibay et al, 2017;Na Kim et al, 2017).…”
Section: Practical Considerations Of Stem Cell Transplantation Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, while IV injection of stem cells may not be the optimal method for direct cell replacement, it has instead the potential to be highly effective for cells which primarily exert their therapeutic effect through long distance paracrine modulation, such as MSCs. Alternatively, intraarterial injection of stem cells has been proposed to prevent the collection of cells in systemic organs and increase the incidence of cells reaching their CNS targets (Walczak et al, 2008;Argibay et al, 2017;Na Kim et al, 2017). However, caution should be taken when using this administration route as it runs the risk of causing microembolisms if the volume and concentration of injected cells are not carefully controlled (Argibay et al, 2017;Na Kim et al, 2017).…”
Section: Practical Considerations Of Stem Cell Transplantation Therapymentioning
confidence: 99%
“…Alternatively, intraarterial injection of stem cells has been proposed to prevent the collection of cells in systemic organs and increase the incidence of cells reaching their CNS targets (Walczak et al, 2008;Argibay et al, 2017;Na Kim et al, 2017). However, caution should be taken when using this administration route as it runs the risk of causing microembolisms if the volume and concentration of injected cells are not carefully controlled (Argibay et al, 2017;Na Kim et al, 2017).…”
Section: Practical Considerations Of Stem Cell Transplantation Therapymentioning
confidence: 99%
“…Regarding intravascular delivery methods, viable stem cells may not pass filtering organs, such as the lungs, liver, and spleen after IV administration. However, some studies promote the use of IA for stem cell administration as the shortest route toward the lesion, with improving cell engraftment and survival (Na Kim et al, 2017 ). The current animal studies or clinical trials did not systematically assess or report adverse events associated with the delivery route chosen.…”
Section: Stem Cell Transplantationmentioning
confidence: 99%
“…The sporadic neurodegenerative disease multiple system atrophy affects the cells of the central and autonomic nervous system and currently suffers from a lack of effective therapeutic options. For this reason, researchers from the Phil Hyu Lee laboratory (Yonsei University, Seoul, South Korea) sought to assess the effectiveness of MSC‐based neuroprotective therapy in an animal disease model administered through an alternative route . Encouragingly, Kim et al demonstrated the feasibility of intra‐arterial administration of MSCs and an overall improvement in striatal and nigral neuronal viability and motor behavioral performance in affected mice.…”
Section: Related Publicationsmentioning
confidence: 99%